Nerita chameleon as biomonitoring agent for Pb, Cd, Cu and Zn in Malaysian intertidal rocky shore environment - Miskon, Mohd Fuad; Mohd Shazali, Noor Azhar; Mohamad, Faridah; Yunus, Kamaruzzaman (Oriental Scientific Publishing Co., 2015)
Pb, Cd, Cu and Zn in the soft tissue of Nerita chameleon from particular rocky shore sites along the east coast of Peninsular Malaysia were investigated. Samples were measured using ICP-MS with standard configuration. The metal accumulation patterns indicate consistent enrichment of essential metals. Locations with relatively high concentrations of the contaminant metals Pb, Cd and Cu are related to their close proximity to industrial activities and urban sites. Comparison with maximum permissible limits of toxic metals in food indicated the values were well within safety levels.